The Use of Virtual Reality in Crime Scene Investigation - Dimovski, Darko T (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The author points out at the beginning that crime scene investigators are responsible for the identification, collection, storage and packaging of physical evidence at the crime scene, which is the basis for conducting the investigation. Lately, it has come to the point that when working at a crime scene, advanced technologies are used with the aim of creating a virtual reality that should make the work of investigators easier. In this connection, the author defines the concept of virtual reality in the continuation of the work, while he deals specifically with its types. The next part of the paper is dedicated to the ways of viewing the crime scene through virtual reality. The last part of the paper refers to the use of virtual reality by students during education.
Keywords: crime scene; virtual reality; trial; student